Penerapan Profile Matching Pada Sistem Pendukung Keputusan Seleksi Calon Penerima Bantuan Program Keluarga Harapan (PKH) Pada Dinas Sosial Kabupaten XYZ - bachtiar, frans; Elizabeth, Triana (Universitas Multi Data Palembang, 2024)
XYZ Service is one of the government agencies which has the task of protecting the community in the field of Social Welfare and has various assistance programs for the community. In activities at the XYZ Service, one of the main problems is the difficulty in determining potential recipients of the Family Hope Program (PKH) and in the process of determining, manual use results in the response to making announcements often being delayed. The aim is to make selection easier in order to produce recommendations for potential aid recipients quickly and efficiently and reduce subjective assessments. The method used is the profile matching method, which is a method that compares the GAP between alternative values ​​and criteria. The system development method uses RUP (Rational Unified Process). The focus of this method is an iterative development process. The information system built is a web base using the PHP programming language and using the Laravel framework and supporting libraries and using a MySQL database. The results of this Decision Support System help the department in determining recommendations for potential aid recipients.